The economic importance of nanotechnology - نجمالدين, عدنان كريم; عباس, علي مهدي (Journal of Economics and Administrative Sciences, 2016)
AbstractToady technology Nano since it launched human Alivia third interest and anticipation unusual and that by the decision-makers in the world's governments and its institutions and research departments productivity, especially after the US Congress enact a law (the National Initiative for Tknlojba nanotechnology in the United States of America) and the allocation of large sums of money To support this initiative, the research aims to shed light on the concept of technology nanotechnology, which is technology atheist and the twentieth century, and reflect its economic importance and in order to reach the objectives of the research has been the division of research into several axes has been allocated the first axis and the second to review the conceptual and historical framework for nanotechnology, either axis III and IV has been reviewing the methods for preparation of nanomaterials and nano-scale, while the fifth discussed the economic importance of the axis of the nano-technology research and finally has reached a number of conclusions and recommendations.